Isotherm Dan Kinetika Adsorpsi Logam CU Menggunakan Adsorben Serbuk Kulit Udang Dengan Variasi Konsentrasi Adsorbat Dan pH Larutan - M. Rafi Yunanda; Yelmida A; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Adsorption is a process in which solute liquids accumulate on the adsorbent surface and form a thin layer of atoms or molecules. The adsorbent used was shrimp shell powder. Utilization of the adsorptionprocess in the absorption of Cu metal is useful for determining the isotherm model and adsorption kinetics. In this study the adsorption process was carried out by varying the concentration of adsorbate(10, 20 and 30 ppm) and the pH of the Cu metal solution (5, 7 and 9) at room temperature. The largest adsorption capacity occurred at the adsorption pH of 5 and the initial solution concentration of 10 ppmwith an adsorption capacity value of 88.28%. The isotherm model of the Cu metal adsorption process follows the Harkins Jura isotherm equation with R2 value of 0.9990. The kinetics of the Cu adsorptionprocess followed the Elovich kinetics model with a value of R2 0.9914 and a constant adsorption rate of 0.631 at an adsorbate concentration of 10 ppm and a pH of 7 Cu metal solution.Keywords : Adsorbent, Adsorption, Isotherm, Kinetics, pH